The Role of the Crown in British Constitution - A. A. Polyakova (Vestnik MGIMO-Universiteta, 2013)
The article introduces the readers to the problem of the role of the monarch in the British constitutional system. This research covers the subject of the British Constitution and Law, it explains the differences between the notions “crown” and “king/ queen”, revealing their peculiarities. The reader can find a summary of a deep analysis of the constitutional system, its functions and features.